2012
DOI: 10.1038/nature10967
|View full text |Cite
|
Sign up to set email alerts
|

An Archaean heavy bombardment from a destabilized extension of the asteroid belt

Abstract: The barrage of comets and asteroids that produced many young lunar basins (craters over 300 kilometres in diameter) has frequently been called the Late Heavy Bombardment (LHB). Many assume the LHB ended about 3.7 to 3.8 billion years (Gyr) ago with the formation of Orientale basin. Evidence for LHB-sized blasts on Earth, however, extend into the Archaean and early Proterozoic eons, in the form of impact spherule beds: globally distributed ejecta layers created by Chicxulub-sized or larger cratering events4. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
343
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(370 citation statements)
references
References 120 publications
17
343
4
1
Order By: Relevance
“…Phosphides are the major P mineral in enstatite chondrites, which have recently been proposed as the source of heavy bombardment impactors (22). Corrosion of the meteoritic phosphide mineral schreibersite likely provided the phosphite detected in the present study, because few other sources of phosphite are known, and none was as widespread and voluminous as meteoritic bombardment early in Earth's history (23).…”
Section: Discussionmentioning
confidence: 65%
“…Phosphides are the major P mineral in enstatite chondrites, which have recently been proposed as the source of heavy bombardment impactors (22). Corrosion of the meteoritic phosphide mineral schreibersite likely provided the phosphite detected in the present study, because few other sources of phosphite are known, and none was as widespread and voluminous as meteoritic bombardment early in Earth's history (23).…”
Section: Discussionmentioning
confidence: 65%
“…For instance, Bottke et al (2012) argued that the impactors should have mostly come from the E belt, Appendices are available in electronic form at http://www.aanda.org a hypothesized continuation of the early asteroid main belt to heliocentric distances less than 2 AU. Gomes et al (2005) had found earlier that the main belt itself would have provided roughly half the impactors; the other half coming from the transplanetary, icy planetesimal disk.…”
Section: Introductionmentioning
confidence: 99%
“…One end-member is an intensive LHB model which assumes that most impact basins, including degraded ones, were formed during this short period (e.g., Ryder, 2002). A LHB model with a less intensive mass flux and a broader peak in time has alternatively been proposed based on a dynamical evolution 25 model (e.g., Bottke et al, 2012;Morbidelli et al, 2012). Another hypothesis, which can explain a peak in ages of impact melts without an increase in impact flux, has also been proposed (e.g., Hartmann, 2003); the high rate of early impacts leads to pulverization of early impact melts, and only late impact melts survive.…”
mentioning
confidence: 99%